Uterine inflammation affects the reproductive performance of dairy cows: A review - Molina-Coto, Roger Eduardo; Lucy, Matthew C. (Agronomía Mesoamericana, 2018)
Incidence of post- partum uterine disease is an important concern in dairy cattle, because it affects its reproduction. Therefore, the objective of this review of literature was to generate a multifactorial overview about uterine diseases, and the reproductive performance of dairy cows, from a zootechnical approach. Dairy cows face multiple challenges around parturition. Immune suppression around calving, exposition to trauma and uterine bacterial contamination, metabolic diseases, lactation, and changes in management make dairy cows susceptible to uterine diseases. Most cows are able to eliminate uterine infection after calving, however, some cows keep uterine disease. Uterine disease may show clinical signs, but also silent signs that affect fertility as well. Poor reproductive performance is not caused by those signs by themselves, but due to alterations in ovarian and uterine function. Also, the problem of this silent signs is that farmers become aware of the disease when it has already caused negative effects on the reproductiveperformance. Sometimes, uterine disease is still present at the moment of the first service after calving. Uterine diseasemake it harder for cows to get pregnant because it affects the establishment and maintenance of pregnancy, being another cause for infertility, increasing the cull rate and decreasing incomes from the dairy industry.